ACTIVITIES OF DAILY LIVING - Romero Ayuso, Dulce María (Anales de Psicología / Annals of Psychology, 2007)
The activities of daily living are an interesting topic specially for professional linking to the rehabilitation work. In spite of their social and academic relevance are few specific publications about this. In this manu-script we review the contributions and the perspective of human activity as an object of study from psychology, the taxonomy of activities of daily living and their relations with the abilities to independent live. According to the new approaches, the study of activities of daily living includes three elements: on one hand the individual capacities or abilities, the tasks and the context or environmental; and the other hand the interaction between the subject skills.